Blockchain for ecologically embedded coffee supply chains - Hana Trollman; Guillermo Garcia-Garcia; Sandeep Jagtap; Frank Trollman (Logistics, 2022)
Background: This research aims to identify how blockchain technology could support the ecological embeddedness of the coffee supply chain. Ecological embeddedness is a subset of the circular economy (CE) that demands legitimacy through design changes to product, production and/or packaging for benefits to economic actors and the environment. This is in contrast with legitimacy as a public relations exercise. Blockchain is a digital transformation technology that is not fully conceptualized with respect to supply chain implementation and the related strategy formulation, particularly in the context of sustainability. Furthermore, the integration of consumers into the CE remains not well understood or researched, with the main focus of CE being the cycling of resources. Methods: This research employs a qualitative case study methodology of the first coffee business in the USA to use blockchain technology as an exemplar. Gap analysis is then applied to identify how blockchain could be used to advance from the current state to a more sustainable one. Results: Findings indicate that the implementation of blockchain is not ecologically embedded in the example studied. Conclusions: The extension of blockchain technology to consider the by-products of production and valorizable waste throughout the supply chain as assets would support ecologically embedded CE for coffee.
Keywords: 650; blockchain; circular economy; coffee; ecological embeddedness; supply chain; sustainability